النظام القانوني للتفويض المرفق العمومي - حسينات, ادم; رميته, احمد (جامعة الوادي university el-oued, 2022)
يخضع اطراف عملية التفويض الى القانون الذي يعد مرجع الأول في هذه العملية الا انه هذه الأخيرة تكون تحت رقابة مختلفة سواء من جانب الإداري او القضائي او غيرها فتكون الرقابة على أساس نوع التفويض والمسائل المتعلقه به. كما ان التفويض هو احدى طرق تسيير المرافق العام حيث تلجا اليه السلطات العمومية لاسيما المحلية عندما تلاحظ بانه الأسلوب الأمثل لادارة هذه المرافق. كما أولى المشرع الجزائري لعقود تفويض المرافق العامة تنظيم قانوني كبير الذي يوضح العديد من الجوانب الإجرائية الواجب اتباعها وامتثال لها من اجل تسيير المرفق العام. ان حصر التفويض بالمرفق العمومية المحلية هذا يؤدي الى انغلاق عن الكفاءاة الأجنبية.The parties to the delegation process are subject to the law, whichis the first reference in this process, but the latter isunderdifferent supervision, whetherfrom the administrative, judicial or otherside. The control isbased on the type of delegation and related issues. Also, delegationis one of the methods of managing public utilities, as the public authorities, especially the local ones, resort to itwhenthey notice thatitis the best method for managingthese utilities. The Algerian legislatoralsoassigned to public utility contracts a large legalregulationthat clarifies manyprocedural aspects to befollowed and compliance with in order to run the public utility. Limiting the mandate to this local public utility leads to a shutdown of foreigncompetencies.
مذكرة ماستر
Keywords: التفويض- المرفق العام- القانون- أطراف العملية; Authorization - General Facility - Law - Parties to the process